1991
DOI: 10.1007/bf02660155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated drying temperature on rapeseed oil quality

Abstract: Effect of rapeseed drying temperature on oil quality was investigated over the range 50-250°C. Total oil content was not significantly affected at 5% probability. Amounts of free fatty acids were significantly affected but remained much below the maximum permissible limit. Oil color was also significantly affected but had no specific trend of variation with temperature, and visual differentiation was difficult. Further, visual cracks and blackening were observed in rapeseeds dried at 250°C. Based on this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…So, the drying parameter, k and the drying exponent, n, were found as 0.083331 and 0.463331, respectively. Since it was reported that the drying parameter, k, is constant and not dependent on the temperature throughout the drying process (Pathak, Agrawal, & Singh, 1991a, 1991bWhite et al, 1981) and the drying exponent, n, is between 0 and 1 (Yagcıoglu, 1999); new values for drying exponent, n, were calculated with the help of Eq. (5) assuming drying parameter, k, was constant and equal to 0.083331 and using the values of MR at 10 min intervals.…”
Section: Experiments and Mathematical Modellingmentioning
confidence: 99%
“…So, the drying parameter, k and the drying exponent, n, were found as 0.083331 and 0.463331, respectively. Since it was reported that the drying parameter, k, is constant and not dependent on the temperature throughout the drying process (Pathak, Agrawal, & Singh, 1991a, 1991bWhite et al, 1981) and the drying exponent, n, is between 0 and 1 (Yagcıoglu, 1999); new values for drying exponent, n, were calculated with the help of Eq. (5) assuming drying parameter, k, was constant and equal to 0.083331 and using the values of MR at 10 min intervals.…”
Section: Experiments and Mathematical Modellingmentioning
confidence: 99%
“…The increases in health-promoting factors are the main reasons for the optimization of processing parameters in order to produce high-quality rapeseed oil. The impact of optional tempering and hulling treatments of the seed [12], drying temperature [13], and processing conditions [14,15] on rapeseed oil quality have been studied. It was determined that the oxidative stability increased and the triglyceride content decreased in pressed rapeseed oil with increased heat treatment of the seed before pressing.…”
Section: Introductionmentioning
confidence: 99%
“…The number of free fatty acids grows and the oxidation process of fat intensifies (Gawrysiak-Witulska et al, 2009). An increase in the drying temperature to above 93°C causes an increase in the content of free fatty acids in the oil (Pathak et al, 1991). Matthäus (2013b) draws attention to the fact that the moisture of seeds that are cold-pressed to produce oil also has a significant impact on the stability of the product.…”
Section: Resultsmentioning
confidence: 99%